Exploring Diversity in Socioeconomic Inequalities in Health Among Rural Dwelling Canadians. Issue 2 (24th December 2014) - Janzen, Bonnie; Karunanayake, Chandima; Pahwa, Punam; Dyck, Roland; Rennie, Donna; Lawson, Josh; Pickett, William; Bryce, Rhonda; Hagel, Louise; Zhao, Guangming; Dosman, James; on behalf of the Saskatchewan Rural Health Study Team
Abstract Purpose To describe the patterning of socioeconomic inequalities in health among rural dwelling women and men in a Canadian province, exploring diversity in associations by measure of socioeconomic position, health outcome, and demographic characteristics. Methods Baseline data from the Saskatchewan Rural Health Study was used, an ongoing prospective cohort study examining the health of rural people in Saskatchewan, Canada. Of the 11, 004 eligible addresses, responses to mailed questionnaires were obtained from 4, 624 (42%) households, representing 8, 261 women and men. Multiple logistic regression was the primary method of analysis; generalized estimating equations were utilized to account for household clustering. Associations between 5 health outcomes (self‐rated health, chronic obstructive lung disease, diabetes, heart attack, high blood pressure) and 4 indicators of socioeconomic position (income, education, financial strain, occupational skill level) were assessed, with age and gender as potential effect modifiers. Findings With the exception of occupational skill level, socioeconomic position (SEP) indicators were strongly and inversely related to most health outcomes, often in a graded manner. Associations between SEP and several health outcomes were weaker for older than younger participants (heart attack, high blood pressure, lung disease) and stronger among women compared to men (high blood pressure, lung disease). Conclusions The patterning of SEP‐health associations observed in this rural Canadian sample suggests the need for health promotion strategies and policy initiatives to be broadly targeted at individuals and families occupying a wide range of socioeconomic circumstances.